COMBINATION OF ULTRASOUND THERAPY, MUSCLE ENERGY TECHNIQUE, AND SUSTAINED NATURAL APOPHYSEAL GLIDES IN NON-SPECIFIC NECK PAIN – A CASE SERIES - Ni Komang Ayu Juni Antari; Anak Agung Gede Angga Puspa Negara; Made Hendra Satria Nugraha (Journal of Vocational Health Studies)
Background: Non-specific neck pain is a common neuromusculoskeletal problem and affects about two thirds of people worldwide. Purpose: To find out the efficacy of the combination therapy in individuals with non-specific neck pain. Case: The intervention was given in 12 sessions (3 times per week for 4 weeks) with the total duration of therapy per session is 20 minutes. The sequence of interventions includes: ultrasound therapy, application of muscle energy techniques, and SNAGs mobilization. Evaluation of therapy in the form of pain was measured by a visual analogue scale and the range of motion of the cervical spine’s lateral flexion was measured by a goniometer. Result: The results of the case series showed a decrease in pain scores from an average of 5.67 to 2.73. In the range of motion of the cervical spine’s lateral flexion there was an increase from an average of 30 degrees to 36 degrees. Conclusion: The combination of ultrasound therapy, muscle energy technique, and sustained natural apophyseal glides provided benefits in reducing pain and increasing the range of motion of the cervical spine’s lateral flexion in individuals with non-specific neck pain. This case series can be used as a preliminary study to develop further research with experimental methods in proving the effectiveness of the combination therapy in treating non-specific neck pain.